Highly effective bacterial agents against Cimbex quadrimaculatus (Hymenoptera: Cimbicidae): isolation of bacteria and their insecticidal activities - Cakici, Filiz Ozkan; Ozgen, Inanc; Bolu, Halil; Erbas, Zeynep; Demirbag, Zihni; Demir, Ismail (Springer, 2015)
Cimbex quadrimaculatus (Hymenoptera: Cimbicidae) is one of the serious pests of almonds in Turkey and worldwide. Since there is no effective control application against this pest, it has been a serious problem up to now. Therefore, we aimed to find an effective bacterium that can be utilized as a biocontrol agent against C. quadrimaculatus in pest management. We isolated seven bacteria from dead and live C. quadrimaculatus larvae, and evaluated the larvicidal potency of all isolates on the respective pest. Based on the morphological, physiological, biochemical and molecular properties (partial sequence of 16S rRNA gene), the isolates were identified to be Bacillus safensis (CQ1), Bacillus subtilis (CQ2), Bacillus tequilensis (CQ3), Enterobacter sp. (CQ4), Kurthia gibsonii (CQ5), Staphylococcus sp. (CQ6) and Staphylococcus sciuri (CQ7). The results of the larvicidal activities of these isolates indicated that the mortality value obtained from all treatments changed from 58 to 100 %, and reached 100 % with B. safensis (CQ1) and B. subtilis (CQ2) on the 3rd instar larvae within 10 days of application of 1.89 x 10(9) cfu/mL bacterial concentration at 25 A degrees C under laboratory conditions. Findings from this study indicate that these isolates appear to be a promising biocontrol agent for C. quadrimaculatus.
Keywords: Cimbex quadrimaculatus; Cultivable bacterial flora; Bacillus; Biocontrol